Kosakata Serapan Bahasa Jepang dalam KBBI: Analisis Struktur dan Makna - Jerniati I. (Ranah: Jurnal Kajian Bahasa, 2019)
This papper aims to describing loan words of Japanese language in KBBI (Indonesian Dictionary). The research approach uses structural analysis which assumes that part of speech or vocabulary could be described through its structural characteristic. Besides that, the writer uses supporting theory like lexical and grammatical meaning. Moreover, the analysis method is using descriptive analysis in order to describe empirically based on situation or facts that existed and explained. The main data is Indonesian Dictionary . The result of analysis shows that: (1) Morphological structure of Japanese language vocabulary in Indonesian Dictionary consists of two, base form and derivation form. Base form is Japanese language words that have been absorbed in Indonesian language (found in Indonesian Dictionary) and could be the base of derived form, whilst derivation form is Japanese vocabulary that has undergone affixation process (prefix ber- and pe-) or compound process that combines loan words of Japanese language and Indonesian words. (2) There are three part of speech of Japanese language found in Indonesian Dictionary. Namely; noun, verb, and adjective. (3) The meaning of the words exposed in analysis is lexical and grammatical meaning. ABSTRAKPenelitian ini bertujuan mengungkapkan masalah kosakata serapan bahasa Jepang dalam KBBI (Kamus Besar Bahasa Indonesia).Penelitian ini menggunakan pendekatan analisis struktural yang dapat mendeskripsikan kelas kata atau kosakata melalui ciri strukturalnya. Selain itu, penulis juga menggunakan paradigma yang mendukung teori makna leksikal dan makna gramatikal. Selanjutnya, penelitian ini menggunakan metode deskriptif analitis yang bertujuan mendeskripsikan secara empiris berdasarkan situasi atau fakta yang ada dan memaparkan dengan apa adanya. Sumber data utama berasal dari KBBI (2016). Hasil penelitian menunjukkan (1) struktur morfologi kosakata bahasa Jepang dalam KBBI ada dua, yaitu struktur kata dasar dan struktur kata turunan. Kata dasar tersebut adalah kosakata bahasa Jepang yang telah diserap dalam bahasa Indonesia  (menjadi penghuni KBBI) dan dapat menjadi dasar bentukan kata, sedangkan kata turunan adalah kosakata bahasa Jepang yang dapat atau telah melewati proses afiksasi (prefiks ber- dan  pe-) atau telah melewati proses pemajemukan yaitu penggabungan kosakata serapan bahasa Jepang dengan kosakata bahasa Indonesia. (2) Kelas kata bahasa Jepang dalam KBBI ada tiga, yaitu  nomina,  verba, dan   adjektiva.  (3) Makna kata yang terungkap dalam analisis adalah makna leksikal dan makna gramatikal.